Neuro-fuzzy modelling and control of multistage dynamic processes that depend on inputs with uncertainty elements - Zhbanova N. Yu. Nataljya Yurjevna; Kravets O. Ya. Oleg Yakovlevich; Grigoriev M. G. Mikhail Georgievich; Babich L. N. Lyudmila Nikolaevna (2015, 2015)
Title screen